Chromatographic analysis and analgesic assay of Alpazoti (Chenopodium ambroisiodes Linn. - Aguilar, Liezl M.
The leaf of alpazoti (Chenopodium ambroisiodes Linn.) was evaluated for its analgesic activity using the acetic acid-iduced writhing assay. The aqueous extract of leaf showed the highest bioactivity with 87.6316 percent reduction in the number of squirms of albino mice using 100 ug/ml dosages. The crude methanolic extract also showed a percent reduction of 76.4211 percent. DCM and ethyl acetate fractions both exhibited 54.6584 percent reduction, thus were also potent analgesics., Aqueous extract was subjected to further assay determine the most effective concentration among the three concentrations, 1000 ug/ml and 10 ug/ml against three corresponding concentrations of the mefenamic acid which served as the positive control and distilled water as the solvent control. 1000 ug/ml of the aqueous fraction reduced the acetic acid-induced writhes by 90.5983 percent while 100 ug/ml and 10 ug/ml of the fraction exhibited 80.0124 percent, respectively. Chromatographic analysis using TLC method showed that aqueous extract may contain terpenes, alkaloids, phenolic compounds, saponins and cardiac glycosides. Three fractions of similar TLC profiles (A1, A2 and A3) were obtained after vacuum liquid chromatography was carried out on the aqueous fraction. Fraction A2 showed the highest analgesis activity by reducing 80.87 percent of the acetic acid-induced withes. Fractions A1 and A3 exhibited 37.61 percent and 35.00 percent reduction, respectively. Using methanol: ethyl acetate